Differential breeding targets in wheat influence non-target traits related to grain quality, but not crop nitrogen requirement - Guardia-Velarde, Lorena; Liu, Hui; Cope, Jonathan E.; Westerbergh, Anna; Weih, Martin (Frontiers in Agronomy, 2023)
Wheat is considered an established crop with a long breeding history. Its varieties are being developed with differential breeding targets, e.g. high grain yield or high grain protein content. The different breeding targets strongly influence performance in the targeted traits, but may also influence non-target traits related to grain quality, nutrient biofortification potential, and nutrient accumulation. This influence of non-targeted traits may, in turn, affect the environmental performance and ecological sustainability of the crop. The aim of this study was to evaluate the relationships between breeding target traits such as grain yield and grain quality, and non-target traits for three groups of spring wheat varieties differing in breeding targets, i.e. high yield (I), organic high protein (II), and intermediate (III) wheat types. Data from a field trial with nine spring wheat varieties grown under two soil compaction treatments over two years with contrasting weather were used. We found that wheat type affected most target and non-target traits with partly large effect sizes, but not nitrogen (N) uptake efficiency, which reflects the potential N resource requirement of the crop. Associations shown between target and non-target traits will be advantageous for wheat breeding programs. Wheat type and environment had similarly sized effects on grain yield and quality traits. Grain concentrations of various macro- and micro-nutrients were frequently, but not always, correlated, indicating that the potential for nutrient biofortification varied between wheat types and was affected by environmental conditions. The grain and starch yields per accumulated plant N were higher in the wheat varieties bred for high grain yields than those bred for high grain protein content; whilst the protein yield per accumulated whole-plant N was similar across all wheat types despite much higher grain N concentrations in the high-protein varieties. Additionally, most of the evaluated traits tended to preserve their static stability across environments. The results link grain yield and grain quality traits to crop nutrient accumulation aspects relevant for the environmental performance and ecological sustainability of the crop. This link will have implications for the evaluation of non-target effects in breeding strategies, influencing the environmental performance of a crop.